Molecular Modelling And Biological Evaluation Of Peptide Based Inhibitors For Dengue Virus - Ismail, Ahmad Ghazali (2021)
Dengue is recognized as one of the most prevalent arthropod-borne viral diseases in human. In these few decades, the pathogenic dengue virus (DENV) has become a serious threat to global health and the World Health Organization’s (WHO) database shows an increase of reported dengue cases by 800% within the period of 2000 to 2019; with a significant jump from 505,430 cases in year 2000 to over 2.4 million cases in 2010 and to over 4.2 million cases in 2019. Hence a suitable vaccine must be developed as soon as possible. The possible interaction between dengue NS2B/NS3 protease binding site and the suggested peptidic inhibitors using computational method, investigate the suitable peptide length for designing NS2B/NS3 dengue protease inhibitor and evaluate the selected peptides using in-vitro protease assay was tested for this study. The peptide substrate, Arg-Arg-Arg-Arg-Ser- Ala-Gly-Met (RRRRSAGM) from the capsid’s cleavage region was chosen as a starting ligand and the complex three-dimensional structure of the NS2B/NS3 protease homology model from Wichapong et al., 2009 was selected and used as the target molecule in for this study. MOE software was being used for molecular docking in this study. Tripeptide is the most suitable peptide length for designing a peptidic NS2B/NS3pro dengue protease inhibitor. The graph trend Tri 1.3 (Arg-Ser-Ala) and Tri 3.1 (Arg-Ala-Arg) always ranked higher than Tetra 1.2(Arg-Arg-Ser-Ala) eventhough Tetra 1.2 had similar peptide sequence with Tri 1.3. This result even enhances the findings that tripeptide is the more favourable peptide length for designing an NS2B/NS3pro antagonist.